Surviving the Crisis and Austerity: The Coping Strategies of Portuguese Households - Frade, Catarina (2015)
In recent years, Southern European households have been facing acute economic hardship involving falling incomes, rising unemployment, devalued investment portfolios, and a growing burden of debt. This means most households have been forced to make unusual adjustments to their expenditure and living standards. However, Portuguese society has revealed the capacity to deal with austerity through the way households are resorting to self mobilization and solidarity based strategies. These adjustment strategies are inscribed in a cultural framework in which familial values, prevalent in Southern European societies, stand out in supporting a strong, operative welfare society. This feature is confirmed hereby through empirical research on the coping mechanisms mobilized by households, via survey questionnaire and interview techniques.